Comparing and contrasting liberal, communitarian and feminist approaches to resolving tensions between customary and constitutional law: the case of polygamy in Swaziland - Manson, Katherine Elizabeth (Rhodes University, Faculty of Humanities, Department of Political and International Studies, 2009)
Tensions between the individual rights and freedoms found in constitutional bills of rights and the traditionally prescribed social roles and positions articulated in African customary law systems have often been characterised as tensions between communitarian and liberal philosophies. In particular, the notion of gender equality, which is often a feature of the protections offered by constitutional bills of rights, is seen to be in direct opposition to the overtly patriarchal character of many African customs and traditions. This thesis looks specifically at polygamy, long and widely considered in the West to be an oppressive practice premised on the assumed inferiority of women. The analysis considers the implications of polygamy in a particular cultural context, that of the Kingdom of Swaziland, where the newly instituted constitution is often seen to be incompatible with many aspects of Swazi customary law. Here, the tension between the constitutional commitment to gender equality and the persistence of polygamy as a seemingly discriminatory cultural practice forms a lens through which to view the debate as a whole. The theoretical analysis is supplemented by empirical research sourced from local media archives and in-depth interviews conducted with twelve Swazi women, both unmarried and married in polygamous relationships. Communitarian and liberal approaches to resolving this tension are compared, contrasted and finally critiqued from a feminist standpoint. The feminist critique of both communitarianism and liberalism implies that neither ideology promises much for women and affirms the relatively recent feminist suggestion that the key to resolving tensions between constitutional and customary law in general, and to uplifting the social/legal status of women in particular lies in the enhancement of women's democratic participation and the improvement of women's decision-making powers.
Keywords: Human rights -- Swaziland; Constitutional law -- Swaziland; Customary law -- Swaziland; Culture and law -- Swaziland; Women's rights -- Swaziland; Sex discrimination against women -- Swaziland; Polygamy -- Swaziland; Liberalism; Communitarianism